PENGUATAN MODERASI BERAGAMA DI SMA AL-MASTHURIYAH KABUPATEN SUKABUMI UNTUK MENCEGAH TUMBUHNYA RADIKALISME - Rahayu, Hilda Sri; Farhan Hamdalah; Cucu Hodijah; Ajeng Intan Legi Novita Sarip; Amna, Amna (LPPM Universitas Bina Bangsa, 2024)
Religious radicalism has become a problem in various aspects, including the education sector. Islamic boarding schools, function as an important center of Islamic education and must actively contribute to fighting the problem of radicalism The purpose of this community service is to emphasize the importance of instilling the values of religious moderation to curb the rise of radicalism in the pesantren-based high school education environment. Providing information on religious moderation is essential to reduce intolerance, prevent conflict, and prevent extremism in religious practices. This study uses a qualitative methodology for data collection, using interview data collection in a case study approach. The findings show that many students in pesantren are not familiar with the concept of religious moderation, the pesantren community shows considerable enthusiasm for service activities oriented to religious moderation to prevent the growth of radicalism.